Diagnostic Performance of Magnetic Resonance Imaging for Detecting Meniscal Ramp Lesions in Patients With Anterior Cruciate Ligament Tears: A Systematic Review and Meta-analysis. Issue 8 (July 2020) - Koo, Boyeon; Lee, Sun Hwa; Yun, Seong Jong; Song, Jae Gwang
Background: The clinical importance of meniscal ramp lesions in patients with anterior cruciate ligament (ACL) tear has emerged as a major issue. However, the diagnostic accuracy of magnetic resonance imaging (MRI) for detecting ramp lesions has a wide range. Purpose: To perform a systematic review and meta-analysis of the diagnostic performance of MRI for diagnosing ramp lesion in patients with ACL tear. Study Design: Systematic review and meta-analysis. Methods: A literature search of PubMed, EMBASE, and the Cochrane Library was performed based on the revised guidelines for the PRISMA DTA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses of Diagnostic Accuracy Studies) statement. Diagnostic performance studies using MRI as the index test and arthroscopy as the reference standard for ramp lesion were included. Bivariate and hierarchical summary receiver operating characteristic modeling was used to evaluate the diagnostic performance. Meta-regression analyses were performed to identify potential sources of heterogeneity. Results: The review and meta-analysis included 9 studies from 8 articles (883 patients with ACL tear and reconstruction). The summary sensitivity, summary specificity, and area under the hierarchical summary receiver operating characteristic for ramp lesion were 0.71 (95% CI, 0.59-0.81), 0.94 (95% CI, 0.88-0.97), and 0.90 (95% CI, 0.87-0.92), respectively. Among the potential covariates, magnet strength ( P < .01), patient knee position ( P = .04), and MRI interpreter ( P = .04) were associated with heterogeneity in terms of sensitivity, whereas magnet strength ( P = .03) was associated with heterogeneity in terms of specificity. Conclusion: MRI demonstrated moderate sensitivity and excellent specificity for diagnosing ramp lesion. Routine arthroscopic assessment is recommended for the presence of ramp lesion, regardless of whether it is suspected on MRI. Further clinicoradiological studies of diagnostic algorithms are needed for identifying ramp lesion, including high-resolution MRI with appropriate knee position.